2010
DOI: 10.1055/s-0030-1249059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visfatin on Proliferation and Collagen Synthesis in Rat Cardiac Fibroblasts

et al.

Abstract: The proliferation of cardiac fibroblasts (CFs) and excessive extracellular matrix protein accumulation are the basic pathological processes of myocardial fibrosis. Visfatin is a novel adipokine involved in the regulation of inflammatory cytokines, however, the effects of visfatin on proliferation and collagen synthesis of CFs are unclear. The aim of this study was to determine whether visfatin has any effect on the proliferation and collagen synthesis in rat CFs. Incorporation of [ (3)H]-thymidine and [ (3)H]-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…The phosphoinositol 3-kinase (PI3K)/AKT pathway is frequently activated in AML, [16][17][18] and it is known that NAMPT induces AKT phosphorylation. 19,20 We did not detect any changes in the levels of phospho-PI3K p85 (Tyr 458) or expression of total PI3K p85 protein in HL-60 cells treated with FK866 or AC93253 compared to DMSO-treated control cells (Online Supplementary Figure S2). However, after inhibition of NAMPT or SIRT2 with FK866 or AC93253 we did find reduced phospho-AKT levels ( Figure 4A).…”
Section: Inhibition Of Nampt or Sirtuin 2 Inactivates Akt And Activatmentioning
confidence: 83%
See 1 more Smart Citation
“…The phosphoinositol 3-kinase (PI3K)/AKT pathway is frequently activated in AML, [16][17][18] and it is known that NAMPT induces AKT phosphorylation. 19,20 We did not detect any changes in the levels of phospho-PI3K p85 (Tyr 458) or expression of total PI3K p85 protein in HL-60 cells treated with FK866 or AC93253 compared to DMSO-treated control cells (Online Supplementary Figure S2). However, after inhibition of NAMPT or SIRT2 with FK866 or AC93253 we did find reduced phospho-AKT levels ( Figure 4A).…”
Section: Inhibition Of Nampt or Sirtuin 2 Inactivates Akt And Activatmentioning
confidence: 83%
“…NAMPT (visfatin) has recently been shown to induce AKT phosphorylation in endothelial cells and in cardiac fibroblasts. 19,20 AKT phosphorylates and thereby inhibits a serine-threonine kinase glycogen synthase kinase 3β (GSK3β). 21 GSK3β is a well-known inhibitor of Wnt signaling.…”
Section: Introductionmentioning
confidence: 99%
“…This adipokine was found to stimulate synovial fibroblasts to secrete proinflammatory cytokines and matrix metalloproteinases [50]. More recently, visfatin was reported to increase DNA and collagen synthesis in cardiac fibroblasts, suggesting its role in myocardial fibrosis [51]. Data on hepatic fibrogenesis are awaited.…”
Section: Resistin and Other Adipokinesmentioning
confidence: 99%
“…These authors suggested a protective role of adiponectin against development of coronary artery diseases. On the other hand, visfatin promotes proliferation of cardiac fibroblasts (Yu et al, 2010) and also upregulate endothelial fibroblast growth factor-2 in human endothelial cells (Bae et al, 2009). …”
Section: Role Of Pvat In Fibroblast and Inflammatory Cells Migrationmentioning
confidence: 99%